Plotting the kill and killing the plot : levels of reading in Nabokov’s Pale fire - Iváncsics, Bernát (AMERICANA E-journal of American Studies in Hungary, 2013)
This essay was written under the guidance of Profesor Enikő Bollobás, Eötvös Loránd University, Budapest.